Biases for Vowel Harmony Over Disharmony in Phoneme Monitoring. - Finley, Sara (Language & Speech, 2026)
Previous research exploring the learnability of vowel harmony (a phonetically natural pattern) and vowel disharmony (a phonetically unnatural pattern) has shown mixed evidence for a naturalness bias. This study aims to clarify these mixed results by introducing a more sensitive and indirect measure of learning—a modified phoneme monitoring task. Participants listened to CV-me/CV-mo words and pressed a button to indicate the final vowel (either [e] or [o]). In the first set of trials, participants responded to words that either always obeyed harmony (HarmonyFirst) or always obeyed disharmony (DisharmonyFirst). In the second set of trials, the rule switched. Results from two studies support a learning bias for vowel harmony; participants generally showed greater decreases in response times for harmonic blocks, and greater increases in response time when the rule switched from vowel harmony to disharmony.